Analysis of the Influence of Macroeconomic Factors on Financial Risk - Isnani Attin Nur A'yunin; Risal Rinofah; Alfiatul Maulida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The company's prospects depend on the overall economic situation, therefore the company must consider the macroeconomic environment because investors will take into account several macroeconomic variables that affect the company's ability to generate profits which will affect financial risk. This study uses research objects in consumer cyclicals sub-sector companies listed on the Indonesia Stock Exchange 2018-2022. Consumer cyclicals consists of 14 sectors and the consumer cyclical sub sector consists of 56 companies which are the population, there are 10 companies that researchers make samples for the phenomenon. This study examines whether macroeconomic factors affect the high and low financial risk in consumer cyclicals sub-sector companies listed on the IDX for the 2018-2022 period. The research objective is to determine the macroeconomic factors affecting financial risk in consumer cyclicals sub-sector companies listed on the IDX for the 2018-2022 period. The data analysis method used in this study uses a purposive sampling method, descriptive statistical analysis, classical assumption test, panel data regression analysis, regression model selection, and hypothesis testing using Eviews 13 software. The results of this study indicate that investment has no significant effect on financial risk in the context of asset structure (DAR) or equity structure (DER), but has a significant impact in the long term on the company's long-term debt (LTDR). This may be due to differences in the duration and type of investment made by the company. Long-term investments financed through long-term debt tend to increase financial risk more significantly than short-term or equity-financed investments.